Pengaruh Harga dan Fasilitas Terhadap Kepuasan Konsumen Agen Tour Purple Garage - Ninche Andiny; Yulis Nurul Aini; Mohammad Maskan (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
Price is one of the most critical factors influencing customer satisfaction. Satisfaction is closely linked to customer loyalty and business sustainability. In the service industry, particularly in tourism transportation, the alignment between the price paid and the facilities received is a key benchmark in evaluating service quality. This study aims to analyze the influence of price and facilities on customer satisfaction. This research used a quantitative descriptive approach, with price and facilities as independent variables, and customer satisfaction as the dependent variable. Data were gathered through questionnaires distributed to 100 respondents, selected using purposive sampling. The data were analyzed using multiple linear regression. The research results show that price and amenities have a positive and significant influence on customer satisfaction. Of these two variables, amenities have a greater influence than price. This suggests that customer satisfaction is more influenced by the extent to which the amenities provided meet or even exceed their expectations. The findings indicated that regular evaluation of pricing strategies and continuous improvement of facilities were necessary to meet customer expectations and improve satisfaction effectively.